2022
DOI: 10.3389/fmed.2022.768896
|View full text |Cite
|
Sign up to set email alerts
|

Survival Outcome of Surgical Resection vs. Radiotherapy in Brain Metastasis From Colorectal Cancer: A Meta-Analysis

Abstract: BackgroundThe incidence of brain metastasis from colorectal cancer (CRC) increases along with the greater survival rate for CRC because of the advances in therapeutic modalities. Local treatment strategies for brain metastasis include surgical resection and radiotherapy. Nevertheless, given the incongruent literature, the optimal therapeutic approach remains to be investigated. This study aims to systematically compare the real-world survival outcome of surgical resection and radiotherapy in patients with brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 44 publications
2
14
0
Order By: Relevance
“…The present data additionally reveal that time of BM diagnosis does not significantly impact patient survival measured from the day of BM resection. These results suggest that the intended prognostic benefit of a surgical therapy in these vulnerable patients [7,25] is present in both patients with metachronous and synchronous BM occurrence. Therefore, the authors recommend that surgical decision making in these patients with systemically spread cancer should be a process independent of the time of BM diagnosis.…”
Section: Discussionmentioning
confidence: 87%
“…The present data additionally reveal that time of BM diagnosis does not significantly impact patient survival measured from the day of BM resection. These results suggest that the intended prognostic benefit of a surgical therapy in these vulnerable patients [7,25] is present in both patients with metachronous and synchronous BM occurrence. Therefore, the authors recommend that surgical decision making in these patients with systemically spread cancer should be a process independent of the time of BM diagnosis.…”
Section: Discussionmentioning
confidence: 87%
“…The lack of a significant link in our study is most likely because it only focused on synchronous BMs. But a recent meta-analysis revealed that the primary CRC site had little impact on the OS [ 12 ]. The effect of primary tumor location on the prognosis of patients with BMs of CRC needs further study.…”
Section: Discussionmentioning
confidence: 99%
“…Radiation, surgery, chemotherapy, or a combination of the three were the most prevalent treatments for BMs. Patients who had brain metastasectomy had a longer overall survival time than those who had radiotherapy [ 12 ]. Metastasectomy or multiagent chemotherapy has been linked to a higher overall survival rate [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations